Bioequivalence of Esaxerenone Conventional Tablet and Orally Disintegrating Tablet: Two Single‐Dose Crossover Studies in Healthy Japanese Men. Issue 8 (21st March 2022) - Kurata, Akifumi; Eto, Takashi; Tsutsumi, Junko; Igawa, Yoshiyuki; Nishikawa, Yasuhiro; Ishizuka, Hitoshi
Abstract: We assessed the bioequivalence of a single dose of 5‐mg of esaxerenone administered as an orally disintegrating tablet (ODT) with the conventional oral tablet in healthy Japanese men. This single‐center, open‐label, randomized, two‐drug, two‐stage crossover, single‐dose study was conducted in two parts. In study 1, both formulations were taken with water. In study 2, only the ODT formulation was taken without water. The primary outcome was the evaluation of bioequivalence of the ODT and conventional tablet using the pharmacokinetic (PK) parameters maximum plasma concentration (Cmax ) and area under the plasma concentration–time curve to the last quantifiable time (AUClast ). Plasma concentrations were measured using a validated liquid chromatography/mass spectrometry method and PK parameters were calculated by noncompartmental analysis. The ratios of the geometric least‐squares mean (2‐sided 90% confidence intervals [90%CIs]) for ODT with (study 1) and without (study 2) water to the conventional tablet were 1.03 (1.00–1.07) and 1.01 (0.96–1.06) for Cmax and 1.03 (1.00–1.07) and 0.96 (0.94–0.98) for AUClast, respectively. The 90%CIs fell within the predefined bioequivalence range of 0.80–1.25. Treatment‐emergent adverse events were similar between both formulations. In conclusion, esaxerenone 5‐mg ODT taken with or without water was bioequivalent to a single 5‐mg conventional oral tablet.